Historical Paths and the Growth of Baghdad Old Center (Journal of Engineering, 2013)
Urban growth of cities is connected with three related problems, the first one, is the deterioration of the center, which is a mark for historical origin. The second is the emergence of city edge, which contradicts by the center. The third one is the rapid semi urbanism of the edge. Literature review showed that Baghdad historical center (Old Rusafa and Karkh) had grown in four morphological stages, during which main paths had been changed from those which were perpendicular to the river front to those parallel to it. Research problem is that “there is a knowledge gap about the direction and origin of paths within Baghdad old center, after its growth”. The first research hypothesis is, “the direction of paths within old Baghdad center had been changed from those perpendicular to the river to parallel to it, then to a grid system by the effect of streets cut through and bridges constructions”. The second research hypothesis is that, “New paths (streets) which had been cut through old center had an origin within the historical paths”.The research aims to verify from the change in paths direction within old center, also from the origin of new streets in relation with historical paths. Research found that some new streets within Old Rusafa and Karkh, which are parallel to the river, existed as historical paths, according to the integration genotype of this center within the four morphological stages.